Once Upon a Time in Iraq - Bluemel, James and Mansour, Renad (London BBC Books, 2021)
In war, there is no easy victory. When troops invaded Iraq in 2003 to topple Saddam Hussein's regime, most people expected an easy victory. Instead, the gamble we took was a grave mistake, and its ramifications continue to reverberate through the lives of millions, in Iraq and the West. As we gain more distance from those events, it can be argued that many of the issues facing us today - the rise of the Islamic State, increased Islamic terrorism, intensified violence in the Middle East, mass migration, and more - can be traced back to the decision to invade Iraq. In Once upon a time in Iraq James Bluemel collects first-hand testimony from those who lived through the horrors of the invasion and whose actions were dictated by such extreme circumstances. It takes in all sides of the conflict - working class Iraqi families watching their country erupt into civil war; soldiers and journalists on the ground; American families dealing with the grief of losing their son or daughter; parents of a suicide bomber coming to terms with unfathomable events - to create the most in-depth and multi-faceted portrait of the Iraq War to date. Accompanying a major BBC series, James Bluemel's book is an essential account of a conflict that continues to shape our world, and a startling reminder of the consequences of our past decisions.
Include Color Illustrations and Index
Keywords: Iraq -- Influence (Literary, artistic, etc.) -- Psychological aspects